Implementasi Konvensi PBB Menentang Peredaran Gelap Narkotika dan Psikotropika Pasal 32 Ayat 2 Terhadap PERMENKES No. 5 Tahun 2023 - Arya Wiguna, Yudha; Sitompul, Nasir (UNES Law Review, 2024)
Paragraph 2 of Article 32 of the United Nations Convention Against Illicit Traffic in Narcotic Drugs and Psychotropic Substances mandates that member states implement necessary measures to penalize adequately serious criminal offenses related to drug trafficking. The paragraph explicitly states in the UN Convention on Narcotics that measures must be taken by each state party to ensure the imposition of penalties for such offenses. The present study employs normative research methods, which encompass various terminologies such as legal, positive legal, doctrinal legal, and pure legal research methods. Focused on written laws (laws in books) or societal customs, normative legal research typically utilizes secondary data, which includes primary, secondary, and tertiary legal materials. Narcotics and psychotropic substances, often produced through agricultural or chemical methods, are frequently processed illegally in concealed laboratories or isolated locations. Trafficking in these prohibited substances involves their illegal production, distribution, and sale, adversely affecting both individual health and societal welfare. Furthermore, the Convention on Narcotics, specifically Article 32 Paragraph 2, has significantly enhanced international cooperation in combating the trafficking of drugs and psychotropic substances in Indonesia. Through strict law enforcement, intelligence sharing, and cross-border operational cooperation, Indonesia can more effectively counter drug trafficking syndicates.